Intensive care management of Gitelman syndrome: A rare case - Das, Subhankar; Kumari, Silky; Kataria, Yuvika; Sahanawaz, Mohammad (Indian Journal of Case Reports, 2024)
Gitelman syndrome (GS) is an autosomal-recessive disorder distinguished by hypokalemia, hypomagnesemia, and hypocalciuria. Elderly people and women of childbearing age are highly affected by GC. Not much evidence is known about its effects on maternal and fetal outcomes. GS is caused by mutations in the thiazide-sensitive Na-Cl cotransporter gene. Due to its rarity and lack of knowledge, it is susceptible to misdiagnosis or being overlooked. In our case, the patient suffered from recurrent hypokalemia, hypomagnesemia, hypochloraemia, and hypocalciuria with hypotension. After taking proper medication, the patient recovered slowly, and during counseling, the patient was provided a diet chart by nutritionists to avoid recurrent electrolyte imbalances.